Career and academic guidance for American Indian and Alaska Native youth - Shutiva, Charmaine L.; ERIC Clearinghouse on Rural Education and Small Schools. ([Charleston, WV : Clearinghouse on Rural Education and Small Schools, AEL, 2001)
Shipping list no.: 2002-0093-P. Mode of access: Internet.